Le divin Marquis: excès de langage, métaphores en lisière, translative sublimitas - Gastón Elduayen, Luis (Thélème. Revista Complutense de Estudios Franceses, 2009)
Beyond the freudian ways or the reference value of some authors eager for scandals, and without arguing about the excessive value we attach to moral judgements, there is a way to approach Sade´s work, between the uncertain and murky fascination, the blind rejection and the compulsory worship to critics: revisiting Sade in his texts, from the point of view of figure language; in other words, of his work rhetoric-poetic, in an imperative dialectic between the wild language and the screen of analogical refraction. To outline not his philosophical discourse, his arguing words, his style of long baroque period, but his metaphors and figures which sprout pristine, directly from a humus of blood, of coprophagy, of go-betweens, of "closed" and torn vaginas, of sacrilegious orgies, and fuckers'vices. Making metaphors means to transform Sadian writing into the means of sublimation of fiction and of the challenges of the story been narrated.
Keywords: Eroticism; Lubricity; Poetics; Images; Figural dynamism